As práticas mágicas na Península Ibérica nas crônicas e na literatura: um estudo introdutório - Jayo, Graciela Mérida de (Revista de História, 1998)
In the Iberian Peninsula, in spite of their systematic persecution since the time of the Visigothic Empire, magic practices preserved their vitality in the XIIIth century, to the point that Alfonso X of Castile, in the "Siete Partidas", established a prudent compromise accepting such practices when for good purposes. Same practices continued alive in the XVth century. On the other side, with the political strengthening of the Christian kingdoms, Muslims and Jews were segregated accused of magic practices or diabolism.